Temperature-Dependent Network Modules of Soil Methanogenic Bacterial and Archaeal Communities - Liu, Pengfei; Klose, Melanie; Conrad, Ralf (Frontiers in Microbiology, 2019)
Temperature is an important factor regulating the production of the greenhouse gas CH4. Structure and function of the soil methanogenic microbial communities are often drastically different upon incubation at 45°C versus 25 or 35°C, but are also different in different soils. Therefore, we wondered whether different temperatures would create distinct microbial community modules that establish upon incubation at a particular temperature and change upon temperature shift. Therefore, we pre-incubated three different soils under anoxic conditions at three different temperatures and then changed the temperature in a factorial manner. We determined composition, abundance and function of the methanogenic archaeal and bacterial communities using HiSeq Illumina sequencing, qPCR and analysis of activity and stable isotope fractionation, respectively. Network analysis showed that the microbial communities in the different soils were all organized within modules distinct for the three incubation temperatures. Heatmap analysis of operational taxonomic units (OTU) from the different temperature modules gave detailed insights into the community structures and their putative functions. The diversity of Bacteria and Archaea was always lower at 45°C than at 25 or 35°C. A shift from 45°C to lower temperatures did not recover archaeal diversity, but resulted in the establishment of structures and functions that were largely typical for soil at moderate temperatures. At 25 and 35°C, CH4 was always produced by a combination of acetoclastic and hydrogenotrophic methanogenesis. At 45°C, however, only one soil maintained such combination, while the other two soils were devoid of acetoclastic methanogens and consumed acetate instead by syntrophic acetate oxidation coupled to hydrogenotrophic methanogenesis. Syntrophic acetate-oxidizing Thermoanaerobacteraceae were especially abundant in these two soils when incubated at 45°C. However, the archaeal OTUs with putative function in acetoclastic or hydrogenotrophic methanogenesis as well as the bacterial OTUs were usually not identical across the different soils and incubation conditions. Overall, methanogenic function was determined by the bacterial and/or archaeal community structures, which in turn were to quite some extent determined by the incubation temperature, albeit largely individually in each soil. There was quite some functional redundancy as seen by different taxonomic community structures in the different soils and at the different temperatures.